Nondisclosure and Adverse Disclosure as Signals of Firm Value - Teoh, Siew Hong; Hwang, Chuan Yang (Review of Financial Studies, 1991)
We present a model in which some of the firm’s information (“news”) can be disclosed verifiably and some information (“type”) cannot, to show that some firms may voluntarily withhold good news and disclose bad news. We describe an equilibrium in which high-type firms withhold good news and disclose bad news, whereas low-type firms disclose good news and withhold bad news. Under some parameter values, this equilibrium exists when other more traditional equilibria are ruled out by standard equilibrium refinements. The model explains some otherwise anomalous empirical evidence concerning stock price reactions to disclosure, provides some new empirical predictions, and suggests that mandatory disclosure requirements may have the undesirable consequence of making it more difficult for firms to reveal information that cannot be disclosed credibly.